ANALISA KUALITAS INSTRUMEN PENELITIAN PEMETAAN KOMPETENSI GURU BAHASA INDONESIA SMA - Katarina Retno Triwidayati (PGSD Universitas Negeri Medan, 2018)
Teacher competency is one of the important things so that learning objectives can be achieved. By conducting research on competency mapping, teachers can get the right way so that their competencies can be improved and learning objectives achieved. This article is part of the results of research on mapping these competencies. Competency mapping is done by compiling research instruments in the form of tests that refer to the applicable syllabus. The results of the syllabus analysis are then realized in the form of questions. The question is then trialled and analyzed. The results of the study showed that the questions that were feasible to use for the Indonesian language teacher competency mapping test were 20 syllabus oriented multiple choice questions and 7 language questions.Keywords: Mapping, Competence, Research Instruments